Caffeine - An Enigma - Hetal Rathod (Indian Association of Preventive and Social Medicine, 2023)
Considering the growing public health significance of some forms of caffeine use, such as the consumption of energy drinks with high caffeine content that are currently largely unregulated or combinations of caffeine and methamphetamine, the International Classification of Diseases 11 (ICD 11) separates caffeine from other stimulants. A stimulant and diuretic, caffeine is a bitter alkaloid that is mostly found in coffee, tea, cacao, and kola nuts. As a stimulant of the Central Nervous System(CNS) it boosts the body's flow of hormone like cortisol. Caffeine promotes relative brain hypoperfusion by increasing energy metabolism while simultaneously diminishing cerebral blood flow. Caffeine stimulates noradrenaline neurons, and appears to affect releaseof dopamine locally.Caffeine is quickly and nearly entirely (up to 99%) absorbed into the bloodstream after consumption.